Search for heavy resonances decaying into a W or Z boson and a Higgs boson in final states with leptons and b-jets in 36 fb−1 of √s=13 TeV pp collisions with the ATLAS detector - Santos, S. P. Amor dos (2018)
A search is conducted for new resonances decaying into a W or Z boson and a 125 GeV Higgs boson in the νν¯ bb¯ , ℓ±νbb¯ , and ℓ+ℓ−bb¯ final states, where ℓ± = e± or μ±, in pp collisions at s=13 TeV. The data used correspond to a total integrated luminosity of 36.1 fb−1 collected with the ATLAS detector at the Large Hadron Collider during the 2015 and 2016 data-taking periods. The search is conducted by examining the reconstructed invariant or transverse mass distributions of W h and Zh candidates for evidence of a localised excess in the mass range of 220 GeV up to 5 TeV. No significant excess is observed and the results are interpreted in terms of constraints on the production cross-section times branching fraction of heavy W′ and Z′ resonances in heavy-vector-triplet models and the CP-odd scalar boson A in two-Higgs-doublet models. Upper limits are placed at the 95% confidence level and range between 9.0 × 10−4 pb and 7.3 × 10−1 pb depending on the model and mass of the resonance.